KEY FACTORS FOR AGRICULTURAL WASTE MANAGEMENT IN INTEGRATED CROP-LIVESTOCK SYSTEMS USING MICMAC ANALYSIS - Santoso, Vidya Damayanti; Hariyadi; Falatehan, A Faroby (Socio-Economics/Agribusiness Department, 2026)
The integrated crop-livestock farming system has great potential in creating synergy between agricultural production, food security, and environmental sustainability. However, the implementation of integrated agricultural waste management in Gadingkulon Village, Dau Subdistrict, Malang Regency still faces various challenges, particularly in aspects of technology adoption and coordination among stakeholders. This research aims to identify key success factors in integrated crop-livestock agricultural waste management to provide strategic recommendations for sustainable farming system development. The method is used MICMAC (Matrix of Cross-Impact Multiplications Applied to Classification) to analyze the influence strength and dependency of 10 variables divided into three aspects: ecological, social, and economic. The research results show that government regulations and policies are the main driving variables (key drivers), while land use efficiency and environmental quality are positioned as relay variables. The presence of farmer groups, waste management technology, operational costs, community participation, and community income are identified as outcome variables that are highly sensitive to changes in driving variables. The system shows dominance of direct influence with a simple and stable structure, providing strategic clarity that interventions can be focused on the main driving variables.